The Conflict and Balance of Work-Family during the COVID-19 Pandemic - Sulistiowati Sulistiowati (Universitas Pendidikan Ganesha, 2024)
Everyday activities have become very limited during the COVID-19 outbreaks in most countries. Many companies have established work-from-home (WFH) policies to reduce transmission risk. Balancing work and private life sometimes becomes challenging, which has worsened during the pandemic. This research aimed to observe the influence of work-life conflict (WFC) consisting of work impeding family (WIF) and family impeding work (FIW) on Work and Life Balance (WLB) and ascertain gender differences in WLB. Data were collected from 100 respondents (50 men and 50 women) through questionnaires. The inclusion criteria were married couples with occupations, had children and were then doing WFH during an outbreak. This research adopted quantitative methods. Data were analyzed using a multiple-regression test and an independent t-test. The outcomes indicated that the WIF conflict had no statistically remarkable influence on the WLB of workers during the COVID-19 pandemic. The FIW conflict has had a positive and statistically remarkable influence on the WLB of workers during the COVID-19 pandemic. Female workers experience a more significant imbalance in the middle of family and work than that experienced by male workers because of their WFH during the COVID-19 pandemic.